Filsafat Pendidikan Islam: Telaah Epistimologi Ilmu - Mustafa Mustafa (IAIN Manado, 2009)
Philosophy and education are, them, but two stages of the some endeavor; philosophy to think out better values and idealism, education to realize these in life, in human personality. Philosophizing and education are, ten, but two stages of the some endeavor; The Islamic theory of education is fundamentally based upon the Qur’anic concepts. In this theory the door is left open for concepts which come from different fiels of knowledge propided thet they fit the Qur’anic perspective. All elements which be reconciled witch Islamic principles should be excluded..Philosophizing to think out better values and idealism, education to realize these in life, in human personality. The ultimate aim of muslim education lies in the realization of complete submission to Allah on the level of the individual, the community and humanity at large. In Islamic educational field, howewer, there are some prominent figurest who .have highly proposed educational theories in Islam. Baced on this fact, Islamic educational has two sourcesr for their educational process, and therefore, Islamic education must combined in balance they fungtion of school with the rule of society.Kata Kunci: Filsafat-Pendidikan Islam dan Epistimologi ilmu